Synod dla Azji w świetle polskiej prasy katolickiej - Chrobot, Ewelina (Annales Missiologici Posnanienses, 2012)
New challenges for the Church in Asia became the motive for calling by John Paul II the Synod for Asia. It took place in 1998 in Rome (19th of April – 14th of May). The article traced how this synod was portrayed in the Polish Roman Catholic press. The author analyzed relations on the subject of the synod which appeared in the Polish Catholic press. At first she presented what was written in the Polish version of “L’Osservatore Romano” and in the “Bulletin KAI”. This information was compared with the data which appeared in most important Polish Catholic weekly press and in the Polish missionary magazines.